Evaluation of Learning in Islamic Religious Education - Zaman, Badrus; Badrus Zaman, Rahma Maulida Budiati, Khusnawati Alawi Nabilla Alya Nandicha, Fatimatuz Zahro, (STAINU Purworejo, 2024)
Evaluation of learning is very important in the learning process. This is because learning evaluation is used to determine the effectiveness and efficiency of the learning system used. Evaluation of learning includes evaluating the learning process, the learning process, and the learning outcomes themselves. Therefore, it is very necessary for educators and students to understand this. This writing aims to understand the evaluation of learning in Islamic Religious Education. The method used is library research, the technique in collecting data is by searching, collecting, and studying from various sources both books, journals, and existing research. This writing aims to determine the effectiveness of learning evaluation in Islamic Religious Education. A good learning evaluation will make the learning process run well, and vice versa if the learning evaluation is not going well then the learning process will be slightly disrupted.